Religious Experience and Its Transformational Power Qualitative and Hermeneutic Approaches to a Practical Theological Foundational Concept - Müller, Sabrina (De Gruyter, 2023)
The author approaches the phenomenon of 'religious experience' through a qualitative study in which young, urban people from Europe and the USA are empirically examined. It becomes clear that individuals themselves are constructive agents of experience and theology. Religious experience manifests itself as a transformative perspective of hope in the lives of young people.